The impact of merarik kode' on women's educational Trajectories in Central Lombok - Yanasari, Pebri; Pratiwi, Aisyah; Kusniati, Endang; Abdullah, Muhammad Saffuan (UIN Ar-Raniry Banda Aceh, 2026)
This study analyzes marriage practices within the merarik culture (merarik kode’) among Sasak women in Pejanggik Village, Central Lombok, using the Harvard Gender Analysis Framework and Walby’s theory of patriarchy. The study focuses on understanding how early marriage within this cultural tradition influences women’s educational experiences and gender relations in everyday life. This research employed a descriptive qualitative approach with purposive sampling to select participants who had experienced marriage through the merarik tradition. Data were collected through observation, in-depth interviews, and documentation involving Sasak women who married at a young age as well as local stakeholders. The collected data were analyzed using the Miles and Huberman interactive model, including data collection, reduction, presentation, and conclusion drawing. The findings reveal that women who experience merarik kode’ often live within unequal gender relations in which domestic responsibilities are assigned to them despite participation in income-generating activities. Their autonomy and access to resources are restricted, as many decisions require approval from their husbands. In addition, early marriage significantly affects women’s educational trajectories. Many women are forced to drop out of formal schooling, face difficulties in continuing equivalency education, and experience limited access to information and knowledge development. These limitations also influence their capacity in parenting and child education. This study highlights that early marriage within the merarik cultural context contributes to educational inequality and limits women’s opportunities for empowerment and social mobility. Therefore, culturally sensitive educational programs and community-based interventions are needed to increase awareness of women’s education and reduce early marriage practices.